2014
DOI: 10.3389/fimmu.2014.00060
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intestinal Immune Responses through TLR Activation: Implications for Pro- and Prebiotics

Abstract: The intestinal mucosa is constantly facing a high load of antigens including bacterial antigens derived from the microbiota and food. Despite this, the immune cells present in the gastrointestinal tract do not initiate a pro-inflammatory immune response. Toll-like receptors (TLRs) are pattern recognition receptors expressed by various cells in the gastrointestinal tract, including intestinal epithelial cells (IEC) and resident immune cells in the lamina propria. Many diseases, including chronic intestinal infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
116
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 105 publications
1
116
1
2
Order By: Relevance
“…The fish intestine contains the largest part of the immune system, which is constantly exposed to potentially pathogenic bacteria and other toxic elements [1]. Moreover, it has been demonstrated that the impairment of the fish intestinal immune system could lead to pathogen translocation and inflammatory bowel disease [2], thereby decreasing fish growth performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…The fish intestine contains the largest part of the immune system, which is constantly exposed to potentially pathogenic bacteria and other toxic elements [1]. Moreover, it has been demonstrated that the impairment of the fish intestinal immune system could lead to pathogen translocation and inflammatory bowel disease [2], thereby decreasing fish growth performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Microbial signaling affects both homeostatic maintenance of intestinal function as well as circadian control of gastrointestinal function. 5,6 Disruption of the circadian clock, either via dietary restriction or phase shifting (e.g. jet-lag) affects temporal distribution of the gut microbiome constituents.…”
mentioning
confidence: 99%
“…Our analyses suggest that the meat carcinogenic pathway involves activation of TLR1 and TLR10 followed by activation of NF-ĸB-initiated transcription of inflammatory genes (Figure 1). Bacterial cell-surface lipopolysaccharides are ligands for TLR1 activation (48), whereas TLR10 has been suggested as a key mediator of Listeria monocytogenes-induced inflammation (49). L. monocytogenes has become a major foodborne pathogen that can be found in meat and processed foods due to its ability to survive the most common food-processing conditions such as extreme pH, high salt concentration, low water activity, and refrigeration temperatures (50).…”
Section: Discussionmentioning
confidence: 99%